2016
DOI: 10.1080/07929978.2016.1141545
|View full text |Cite
|
Sign up to set email alerts
|

Silicon elicited varied physiological and biochemical responses in Indian mustard (Brassica juncea): a concentration dependent study

Abstract: The present investigation was conducted to evaluate the silicon (Si) mediated responses in different cultivars of Indian mustard (Brassica juncea) and to evaluate if Si could be used as an essential, beneficial, or quasi-essential element for growth and development of these cultivars. Surface sterilized seeds were sown in pots and allowed to germinate under natural environmental conditions. At 10, 12, 14, 16, and 18 days after germination, a range of Si concentrations (0.0, 0.2, 0.4, 0.8 and 1.6 mM) was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The application of silicon prevents these water losses [244]. Moreover, this element also affects the architecture of plant leaves to increase the amount of light interception by leaves [245], thereby improving sclerenchyma, vascular tissues, and vascular sheaths [246,247], and preventing lodging in wheat and rice. This micronutrient can be utilized to stimulate silicification and lignification in thick-walled cells, thicken collenchyma cells, and improve keratinocyte development and enhance cellulose content, as a result increasing lodging resistance in rice [248].…”
Section: Agronomical Managementmentioning
confidence: 99%
“…The application of silicon prevents these water losses [244]. Moreover, this element also affects the architecture of plant leaves to increase the amount of light interception by leaves [245], thereby improving sclerenchyma, vascular tissues, and vascular sheaths [246,247], and preventing lodging in wheat and rice. This micronutrient can be utilized to stimulate silicification and lignification in thick-walled cells, thicken collenchyma cells, and improve keratinocyte development and enhance cellulose content, as a result increasing lodging resistance in rice [248].…”
Section: Agronomical Managementmentioning
confidence: 99%
“…Wang et al [ 172 ] observed that Si element could amplify the photosynthetic rate by altering the leaf structure and the content of chlorophyll in rice plants. In addition, Si element can change the leaf anatomy to capture more light and enhance the light interception in the plant’s leaves and to improve the vascular bundle sheath and sclerenchyma tissues, which help in lodging resistance [ 173 , 174 ]. Another research has concluded that Si could be used as fuel to ignite the process of lignification and silicification for the cell wall and collenchyma cells thickness that increases the development of keratinocyte and cellulose contents resulting in lodging tolerance [ 28 ].…”
Section: Agro-techniques For the Management Of Lodging Stressmentioning
confidence: 99%
“…Overall, the concentration-dependent response of Si is widely observed in crops, including, soybean (Park et al, 2019), rice (Kim et al, 2014), Indian mustard (Rehman et al, 2016), and sugarcane (Frazão et al, 2020). However, the cultivar-dependent response of Si in soybean has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%